2023
DOI: 10.1101/2023.09.06.23295072
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Utilizing ChatGPT to select literature for meta-analysis shows workload reduction while maintaining a similar recall level as manual curation

Xiangming Cai,
Yuanming Geng,
Yiming Du
et al.

Abstract: Background: Large language models (LLMs) like ChatGPT showed great potential in aiding medical research. A heavy workload in filtering records is needed during the research process of evidence-based medicine, especially meta-analysis. However, no study tried to use LLMs to help screen records in meta-analysis. In this research, we aimed to explore the possibility of incorporating ChatGPT to facilitate the screening step based on the title and abstract of records during meta-analysis. Methods: To assess our str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…The paper illustrates how AI, specifically ChatGPT, can assist in various steps of the systematic review process, including evaluating methodologies and extracting data. The study in [13] focuses on the application of ChatGPT in streamlining the literature selection process for meta-analysis in medical research. It outlines a methodology for using ChatGPT to facilitate the screening of titles and abstracts during meta-analysis, aiming to reduce workload while maintaining recall efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The paper illustrates how AI, specifically ChatGPT, can assist in various steps of the systematic review process, including evaluating methodologies and extracting data. The study in [13] focuses on the application of ChatGPT in streamlining the literature selection process for meta-analysis in medical research. It outlines a methodology for using ChatGPT to facilitate the screening of titles and abstracts during meta-analysis, aiming to reduce workload while maintaining recall efficiency.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It outlines a methodology for using ChatGPT to facilitate the screening of titles and abstracts during meta-analysis, aiming to reduce workload while maintaining recall efficiency. The study includes a glioma meta-analysis for validation and discusses the development of a pipeline called LARS (Literature Records Screener) to assess the performance of ChatGPT in this context [13]. It deals directly with improving the efficiency and effectiveness of literature selection and screening in the context of meta-analysis, a crucial step in systematic reviews and research synthesis [13].…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequently, they can utilize ChatGPT to automatically screen records retrieved from databases, obtaining the filtered results . Previous studies suggested that utilizing ChatGPT in the literature selection process for meta-analysis substantially diminishes the workload while preserving a recall rate on par with manual curation [28,[44][45][46][47].…”
Section: Screen the Literaturementioning
confidence: 99%